Communication and organizational learning in adaptation of the Radio Republik Indonesia - Pandan Yudhapramesti; Deddy Mulyana; Eni Maryani; Dian Wardiana Sjuchro (Universitas Padjadjaran, 2021)
Radio Republik Indonesia (RRI) had been the state media during the New Order era. However, since the fall of that regime in 1998, followed by the ratification of the Broadcasting Law Number 32 of 2002, RRI’s status changed to a public broadcasting institution (LPP). The change requires an organizational adaptation process which is not easy in practice. This study finds that communication can be both a driving factor and an obstacle to the adaptation process within the RRI organization. This research aims to explore the operationalization of communication in the adaptation process of the RRI and reveal how the flow of communication builds the relationship between members of the RRI organization; how organizational communication works in the learning process within the organization; and the dynamics of organizational learning in the adaptation process of the RRI organization. The results indicate that the dynamics of communication flows affect the organization’s communication climate. Meanwhile, organizational communication operates in several ways, namely: communication is a means to acquire as well as to conceal knowledge among RRI employees; communication helps the members of the organization understand a phenomenon from different perspectives; communication flows affect the distribution of communications; communication can be an accelerator as well as a barrier to organizational learning abilities. This study suggests further research on the role of communication to promote the internalization values of an organization into strategic decisions and concrete actions and the research on the roles of organizational culture and local culture in organizational adaptation.